2021
DOI: 10.1111/are.15446
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fish stocking density and dietary supplementation of vitamin C and micronutrients (Mn, Zn and Se) on the development of systemic granulomatosis in juvenile meagre ( Argyrosomus regius )

Abstract: Systematic granulomatosis is a chronic disease that affects the majority of farmed meagre (A. regius). Nutritional imbalances and overcrowding can increase the risk to suffer oxidative stress, and consequently, impact the incidence of granulomatosis. In order to evaluate this, juvenile meagre were fed five isolipidic (16.7%) and isoproteic (49.6%) fish meal and fish oil-based feeds prepared by adding different levels of vitamin C, minerals (Mn, Zn, Se) with constant vitamin E and K (300 and 35 mg/kg respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…An increasing amount of evidence has suggested that a high stocking density can induce intracellular redox imbalance, leading to oxidative stress or oxidative damage in many fish species [ 68 , 69 ]. In order to defend against oxidative stress, fish, similar to mammals, have developed an antioxidant defense system consisting of enzymatic antioxidants (e.g., SOD, Gpx and CAT) and non-enzymatic antioxidants (e.g., GSH, Vitamin C, carotenoids and flavonoids) [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing amount of evidence has suggested that a high stocking density can induce intracellular redox imbalance, leading to oxidative stress or oxidative damage in many fish species [ 68 , 69 ]. In order to defend against oxidative stress, fish, similar to mammals, have developed an antioxidant defense system consisting of enzymatic antioxidants (e.g., SOD, Gpx and CAT) and non-enzymatic antioxidants (e.g., GSH, Vitamin C, carotenoids and flavonoids) [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stocking density is also one of the most important factors to consider when rearing fishes in RAS since this most frequently influences growth, water quality, and fish welfare parameters (Oppedal et al 2011, Manley et al 2014, Yang et al 2020. The dependence of fish welfare on stocking density means that determining optimal density is difficult because both too low and too high densities influence growth and fish welfare (Adams et al 2007, Ni et al 2016, Ruiz et al 2021. Reactions to stress factors among sturgeons are not as pronounced as they are in other fish species.…”
Section: Introductionmentioning
confidence: 99%